1982
DOI: 10.1515/zna-1982-1102
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure of Amorphous Metallic Ni81B19

Abstract: The three partial Faber Ziman structure factors as well as the Bhatia Thornton structure factors of the metallic glass NigiBig were evaluated by neutron diffraction experiments using the isotopic substitution method. In one of the investigated specimens the isotopic composition of the components was adjusted in such a way as to make it possible to measure directly with one diffraction experiment the correlation between the metalloid atoms. From the three partial pair correlation functions the atomic distances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(38 citation statements)
references
References 19 publications
3
34
0
1
Order By: Relevance
“…With the R t j, Z, 7 , and the widths a^ of the five distributions given in [15] a total G(R) corresponding to Cu6oZr4o was simulated as sum of five Gaussian curves using the appropriate weighting factors. Mathematical details are described in previous papers [84,95], Figure 6 a (dash dotted curve) shows the result, and one can see that the agreement is poor.…”
Section: Experimental Data From Literaturementioning
confidence: 83%
See 2 more Smart Citations
“…With the R t j, Z, 7 , and the widths a^ of the five distributions given in [15] a total G(R) corresponding to Cu6oZr4o was simulated as sum of five Gaussian curves using the appropriate weighting factors. Mathematical details are described in previous papers [84,95], Figure 6 a (dash dotted curve) shows the result, and one can see that the agreement is poor.…”
Section: Experimental Data From Literaturementioning
confidence: 83%
“…It may be noted that this asymmetric structural behaviour is found to be much more rigorous in metallic glasses of the metal-metalloid type. In this type of glasses direct neighbourhood between the smaller metalloid atoms is avoided and thus the partial metalliod-metalloid structure factor shows a peak at lower (2-values than the main peak of the total X-ray structure factor [84], It is therefore suggested that this asymmetric behaviour, more or less pronounced, is a common feature of all types of metallic glasses.…”
Section: Structure Factorsmentioning
confidence: 93%
See 1 more Smart Citation
“…Medium-range order (MRO) in amorphous metals was first seen 30 years ago, 8 but its physical origin and the specific type of order remained unknown for many years. The ECP model gave the first physical description for the origin of this MRO, and also suggests a particular type of order that can be checked directly with experiment.…”
Section: Medium-range Structurementioning
confidence: 99%
“…Amorphous metals were shown to have significant shortrange atomic order, 7 and since 1982 a surprising degree of medium-range order has been measured. 8 The origin of this order, and its description, also remained a mystery for many years.…”
Section: Introductionmentioning
confidence: 99%